(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2008)
Freedom of expression constitutes one of the essential foundations of a democratic society and one of the basic conditions for its progress and for each individual’s selffulfilment. The European Court of Human Rights, mindful of the importance of the right to freedom of expression on matters of general interest, of the right of civil servants and other employees to report illegal conduct and wrongdoing at their place of work, the duties and responsibilities of employees towards their employers and the right of employers to manage their staff, weighed up the different interests involved in the Case of Guja vs Moldavia, assessing whether the interference with the applicant’s right to freedom of expression, in particular his right to impart information, was «necessary in a democratic society». Public interest involved in the disclosed information, the authenticity of the information disclosed, the damage suffered by the public authority and the motive behind the actions of the reporting employee are the determinant factors in deciding whether the particular disclosure should be protected or not.